Oral treatment with SEW2871, a sphingosine-1-phosphate type 1 receptor agonist, ameliorates experimental colitis in interleukin-10 gene deficient mice. (9th June 2014) - Dong, J; Wang, H; Wu, G; Zhao, J; Zhang, L; Zuo, L; Zhu, W; Gong, J; Li, Y; Gu, L; Li, J
Summary: SEW2871, a selective sphingosine-1-phosphate type 1 receptor (S1P1) agonist, has been shown to be effective in protecting kidneys against ischaemia–reperfusion injury by reducing CD4 + T cell infiltration in mice. However, the effects of SEW2871 on colitis remain unclear. The aim of this study was to investigate the effects of SEW2871 on established colitis in interleukin (IL)-10 gene-deficient (IL-10 –/– ) mice, a murine model of Crohn's disease (CD). SEW2871 was administered by gavage at a dose of 20 mg/kg/day for 2 weeks to IL-10 –/– mice. Severity of colitis, serum amyloid A, tissue myeloperoxidase (MPO), T cells in blood and colon lamina propria (LP) and proinflammatory cytokine productions were evaluated. Furthermore, the phospho-signal transducer and activator of transcription (STAT)-3 (p-STAT-3) expression in lymphocytes isolated from colon LP was also assessed. The 2-week administration of SEW2871 ameliorated established colitis in IL-10 –/– mice, associated with a reduction of serum amyloid A concentration, a decreased colon MPO concentration, a depletion of the peripheral CD4 + CD45 + T cells and a reduction of the homing of T cells into colon LP. Moreover, typical cytokines of T helper type 1 (Th1) and Th17 cells and p-STAT-3 expression were also suppressed by SEW2871 treatment. SEW2871 treatment ameliorates established experimental colitis in IL-10 –/– mice, which may provide a new therapeutic approach for human CD therapy.